Outdoor play : teaching strategies with young children - Perry, Jane, 1955- (New York : Teachers College Press, 2001)
Presents a case study of outdoor play at a California preschool, examining teachers' methods of promoting and supporting pretend play.
Includes bibliographical references (p. 119-122) and index.
Professional
Keywords: Education, Preschool -- Activity programs -- California -- Berkeley -- Case studies; Outdoor recreation for children -- California -- Berkeley -- Case studies; Play -- California -- Berkeley -- Case studies; Social interaction in children -- California -- Berkeley -- Case studies; Outdoor recreation for children -- Case studies; Play -- Case studies; Preschool education -- Berkeley (Calif) -- Case studies; Social interaction in children -- Case studies